Space in language and linguistics: geographical, interactional, and cognitive perspectives - Auer, Peter; Hilpert, Martin; Stukenbrock, Anja; Szmrecsanyi, Benedikt (Linguae & litterae, 2013)
Main description: This book brings together three perspectives on language and space that so far are lacking productive interconnections:a) Language, space, and geography; b) Grammar, space, and cognition; c) Language and interactional spaces. The contributions in this book showcase the thematic and methodological breadth of research on language and space; they are accompanied by commentaries that highlight common threads.
Keywords: Konferenzschrift -- 2009 -- Freiburg; Aufsatzsammlung; Linguistik; Zeit; Raum; Sprachvariante; Mundart; Sprache